Some remarks on a Wiener flow with coalescence - Dorogovtsev, A. A.; Дороговцев, А. А.; Дороговцев, А. А. (Institute of Mathematics, NAS of Ukraine, 2005)
We study properties of a stochastic flow that consists of Brownian particles coalescing at contact time.